Effect of gender on evidence-based practice for Australian patients with acute coronary syndrome: A retrospective multi-site study. Issue 2 (May 2017) - Kuhn, Lisa; Page, Karen; Street, Maryann; Rolley, John; Considine, Julie
Abstract: Background: Early acute coronary syndrome (ACS) care occurs in the emergency department (ED). Death and disability from ACS are reduced with access to evidence-based ACS care. In this study, we aimed to explore if gender influenced access to ACS care. Methods: A retrospective descriptive study was conducted for 288 (50% women, n = 144) randomly selected adults with ACS admitted via the ED to three tertiary public hospitals in Victoria, Australia from 1.1.2013 to 30.6.2015. Results: Compared with men, women were older (79 vs 75.5 years; p  = 0.009) less often allocated triage category 2 (58.3 vs 71.5%; p  = 0.026) and waited longer for their first electrocardiograph (18.5 vs 15 min; p  = 0.001). Fewer women were admitted to coronary care units (52.4 vs 65.3%; p  = 0.023), but were more often admitted to general medicine units (39.6 vs 22.9%; p  = 0.003) than men. The median length of stay was 4 days for both genders, but women were admitted for significantly more bed days than men (IQR 3–7 vs 2–5; p  = 0.005). Conclusions: There were a number of gender differences in ED care for ACS and women were at greater risk of variation from evidence-based guidelines. Further research is needed to understand why gender differences exist in ED ACS care.